Application of low temperature luminescent glaze on Labu Sayong / Siti Noor Azila Noordin - Noordin, Siti Noor Azila (2014)
Sayong fired clay is a raw material for Labu Sayong craft making in Malaysia. Labu Sayong is a pottery where it's functioning as a water vessel which the design and form was adapted from the pumpkin. Basically, the term labu is a pumpkin and Sayong is a location in Kuala Kangsar, Malaysia. Hence, it was called Labu Sayong to signify the origin of the clay and its uniqueness. Originally, Labu Sayong appeared in black with decoration on its surface where the motive of the decoration was inspired from flora and fauna. In present, Labu Sayong is one oft he most iconic of the national heritage. In this thesis, the aim and motivation of the work is to revive the appearance of Labu Sayong by introducing the luminescent effect on its body without compromising its original appearance. Hence, SrAlz04:(Eu z+,Dy +) ceramic compound was employed as a candidate for the luminescent materials. In the preliminary investigation, it was concluded to apply the luminescent materials on the decoration of the Labu Sayong. The SrAlz04:(Eu 2+,Dy +) was successfully synthesized and sintered at 1250°C for 2 hours. In this investigation, the use of glazing technique was introduced as a mean to mount the luminescent materials on Labu Sayong body. This had affected the originality of the Labu Sayong but it was very minimal. In present, there is also modification performed by other craft makers to give an added value to the Labu Sayong. Thus, the low temperature transparent glaze was composed with several recipes as an adhesive to the luminescent materials to the Labu Sayong body. The final recipes used as a mounting adhesive was 80% boric acid, 10% kaolin and 10% silica as sintered at 800oe/O.5 hours. Finally, it was determined that SrAlz04:(Eu z+,Dy +) powder was successfully mounted on the Labu Sayong body via under glaze technique. The glowing of the luminescent materials was successfully measured using a photometer. The highest luminescent effect was 2.509 cd/rrr' for 2 minutes for the sample of on glaze technique. However the longest luminescent effect was 6 minutes with 0.358 cd/rrr' for under glaze sample. In general all samples were faded after 6 minutes. Finally this finding will benefit other researches and ceramic artist to embark on this innovative technique on other product and artwork and also to revive the Labu Sayong appearance as another of the significant national heritage icon as well as to preserve it.